Amorphous Tellurium‐Embedded Hierarchical Porous Carbon Nanofibers as High‐Rate and Long‐Life Electrodes for Potassium‐Ion Batteries. Issue 32 (10th July 2022) - Yu, Dandan; Li, Qinghua; Zhang, Wei; Huang, Shaoming
Abstract: Tellurium (Te) is a promising electrode active material for potassium‐ion batteries due to its intrinsic electrical conductivity and ultra‐high theoretical volumetric capacity. Nevertheless, Te‐based electrodes usually exhibit low capacity at high rates and poor cycling stability caused by the large volume expansion and severe polytellurides dissolution. Herein, hierarchical porous carbon nanofibers (HPCNFs) film is utilized as a multifunctional Te substrate. The free‐standing Te@HPCNFs electrode renders an outstanding K‐ion storage performance with a high‐rate capacity of 1294.4 mAh cm −3 (207.1 mAh g −1 Te ) at 14C and ultra‐long lifespan for 4500 cycles at 7C, and K‐ion full batteries coupled with KSn alloy anode also exhibit good cyclability. Such a superior performance benefits from the space confinement of HPCNFs to load amorphous Te in the micropores for accommodating the volume change, where the interconnected conductive frameworks and residual hierarchical pores enable fast ion/electron diffusion kinetics. In situ UV–vis absorption spectra confirm that the detachment of polytellurides and K2 Te from the electrode is effectively suppressed, and ex situ X‐ray photoelectron spectroscopy analysis reveals the conversion of Te into K5 Te3 and K2 Te. This work presents the significance of porous structure design of carbon matrix to construct high performance Te electrodes, which will be instructive for chalcogens‐based energy‐storage materials. Abstract : Free‐standing amorphous tellurium‐embedded hierarchical porous carbon nanofibers (Te@HPCNFs) are rationally designed as a high‐rate‐capacity and long‐life electrode for potassium–tellurium batteries. The efficient encapsulation of amorphous Te in micropore‐dominated HPCNFs, physical/chemical interactions between the Te and HPCNFs, and strong confinement/adsorption of HPCNFs toward polytellurides and K2 Te alleviate the volume change and shuttle effect, enabling superior rate capability and cycling stability.